CEBPA Mutations in Younger Adults With Acute Myeloid Leukemia and Normal Cytogenetics: Prognostic Relevance and Analysis of Cooperating Mutations - Stefan Fröhling; Richard F. Schlenk; Ina Stolze; Jörg Bihlmayr; Axel Benner; Sylvia Kreitmeier; Karen Tobis; Hartmut Döhner; Konstanze Döhner (2004)
To assess the prognostic relevance of mutations in the CEBPA gene encoding CCAAT/enhancer binding protein alpha (C/EBP alpha) in a large prospective series of younger adults with acute myeloid leukemia (AML) and normal cytogenetics.The entire CEBPA coding region was sequenced in diagnostic samples from 236 AML patients 16 to 60 years of age with normal cytogenetics who were uniformly treated on two consecutive protocols of the AML Study Group Ulm, and CEBPA mutation status was correlated with clinical outcome.CEBPA mutations were detected in 36 (15%) of 236 patients. Twenty-one (9%) of 236 patients had mutations predicted to result in loss of C/EBP alpha function. Remission duration and overall survival (OS) were significantly longer for the 36 patients with CEBPA mutations (P =.01 and P =.05, respectively). On multivariate analysis, wild-type CEBPA was an independent prognostic marker affecting remission duration (hazard ratio, 2.85; P =.01) and OS (hazard ratio, 1.87; P =.04). Analysis of cooperating mutations (both types of activating FLT3 mutations and MLL partial tandem duplications) showed that FLT3 mutations had no significant prognostic influence in patients with CEBPA mutations. Furthermore, there was no significant overlap between the subgroup of patients with CEBPA mutation with predicted loss of C/EBP alpha function and patients with FLT3 or MLL mutations, suggesting that CEBPA loss-of-function mutations define a distinct biologic subclass of AML with normal cytogenetics.Mutant CEBPA predicts favorable prognosis and may improve risk stratification in AML patients with normal cytogenetics.